2017
DOI: 10.1073/pnas.1703779114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic responses of the adrenal steroidogenic regulatory network

Abstract: The hypothalamic-pituitary-adrenal axis is a dynamic system regulating glucocorticoid hormone synthesis in the adrenal glands. Many key factors within the adrenal steroidogenic pathway have been identified and studied, but little is known about how these factors function collectively as a dynamic network of interacting components. To investigate this, we developed a mathematical model of the adrenal steroidogenic regulatory network that accounts for key regulatory processes occurring at different timescales. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 56 publications
7
73
0
1
Order By: Relevance
“…This cyclic pattern is caused by the delay between the activation and negative feedback of the hypothalamus-pituitary-adrenal axis, as was first predicted in a mathematical model and later demonstrated experimentally (Walker et al 2012). The kinetic and dynamic properties of ultradian pulses are not static but are liable to changes for example in association with activation of the immune system and specific diseases (Spiga et al 2017). It was shown that ultradian patterns in the circulation, at least in rodents, are maintained in the brain (Qian et al 2012).…”
mentioning
confidence: 89%
“…This cyclic pattern is caused by the delay between the activation and negative feedback of the hypothalamus-pituitary-adrenal axis, as was first predicted in a mathematical model and later demonstrated experimentally (Walker et al 2012). The kinetic and dynamic properties of ultradian pulses are not static but are liable to changes for example in association with activation of the immune system and specific diseases (Spiga et al 2017). It was shown that ultradian patterns in the circulation, at least in rodents, are maintained in the brain (Qian et al 2012).…”
mentioning
confidence: 89%
“…Despite this fall in ACTH levels, small changes in these basal levels of ACTH initiate large pulses of cortisol, indicating a rapidly induced increased sensitivity of the adrenal cortex to ACTH. This effect has now been investigated in reverse translation studies in rats and complemented with mathematical modelling, which enabled the importance of the dynamic adrenal steroidogenic regulatory network to be characterised 47 .…”
Section: [H1] Hpa Axis and Circadian Rhythmicitymentioning
confidence: 99%
“…As CORT is highly lipophilic it is not prestored in vesicles and is synthesised de novo in response to ACTH. During long-term stress a dissociation between ACTH and CORT secretion develops 93,94 , predominantly via increased adrenal sensitivity to ACTH 47 or non-ACTH mediated mechanisms 94 . This effect is seen in patients undergoing cardiac surgery, who show a marked shift in adrenal responsiveness (figure 1) 46 , reverse translation animal studies suggest this shift arises secondary to changes in the regulation of both stimulatory and inhibitory intra-adrenal signalling pathways 46 .…”
Section: [H1] Stress and Diseasementioning
confidence: 99%
“…In turn, ACTH stimulates the steroidogenesis in adrenocortical cells by binding the melanocortin 2 receptor (MC2R) (21), whereas cortisol and other glucocorticoids exert a negative feedback at hypothalamic and pituitary level, allowing therefore to keep a balance between cortisol requirement and cortisol secretion (22,23) (Figure 1). Furthermore, cortisol synthesis might be also regulated by itself in an auto-feedback loop within the adrenal gland (24,25). The physiological glucocorticoid negative feedback on the HPA axis is exerted upon binding to the glucocorticoid receptor (GR), encoded by NR3C1 gene.…”
Section: The Glucocorticoid Negative Feedbackmentioning
confidence: 99%